Expansion of Human NK Cells Using K562 Cells Expressing OX40 Ligand and Short Exposure to IL-21 - Kweon, SoonHo; Phan, Minh-Trang Thi; Chun, Sejong; Yu, HongBi; Kim, Jinho; Kim, Seokho; Lee, Jaemin; Ali, Alaa Kassim; Lee, Seung-Hwan; Kim, Sang-Ki; Doh, Junsang; Cho, Duck (Frontiers in Immunology, 2019)
Background: Natural Killer (NK) cell-based immunotherapy used to treat cancer requires the adoptive transfer of a large number of activated NK cells. Here, we report a new effective method to expand human NK cells ex vivo using K562 cells genetically engineered (GE) to express OX40 ligand (K562-OX40L) in combination with a short exposure to soluble IL-21. In addition, we describe a possible mechanism of the NK cell expansion through the OX40 receptor-OX40 ligand axis which is dependent on NK cell homotypic interaction. Methods: K562-OX40L cells were generated by lentiviral transduction and were used as feeder cells to expand and activate NK cells from PBMCs in the presence of IL-2/IL-15. Soluble IL-21 was also added in various concentrations only once at the beginning of the culture. NK cells were expanded for 4 to 5 weeks, and the purity, expansion rate, phenotype and function (cytotoxicity, antibody-dependent cell-mediated cytotoxicity (ADCC), cytokine production, CD107a degranulation) of these expanded NK cells were compared to those generated by using K562 feeder cells. Results: The culture of NK cells with K562-OX40L cells in combination with the transient exposure to IL-21 highly enhanced NK cell expansion to approximately 2000-fold after 4 weeks of culture, compared to a 303-fold expansion using the conventional K562 cells. Mechanistically, the OX40-OX40L axis between the feeder cells and NK cells as well as the homotypic interaction between NK cells through the OX40-OX40L axis were both necessary for NK cell expansion. The short exposure of NK cells to IL-21 had a synergistic effect with OX40 signaling for NK cell expansion. Apart from their enhanced expansion, NK cells grown with K562-OX40L feeder cells were similar to those grown with conventional K562 cells in regard to the surface expression of various receptors, cytotoxicity, ADCC, cytokine secretion, and CD107 degranulation. Conclusion: Our data suggest that OX40 ligand is a potent co-stimulant for the robust expansion of human NK cells and the homotypic NK cell interactions through the OX40-OX40L axis is a mechanism of NK cell expansion.